Efektivitas Self Management Terhadap Keterlambatan Menyerahkan Tugas pada Masa Pandemi Covid-19 - Jaenudin Zaen; Dwi Endrasto Wibowo; Sabar Lesmana (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2020)
This study aims to obtain empirical data from information about the effectiveness of the Self Management Technique Group Counseling service at SMP Nurul Iman Sukakarya Bekasi. This quantitative research, using Quasi Experiment Research Method, with research design Non equivalent Control Group Design, population as many as 374 students then sample technique with purposive sampling, research sample is 16 students with 8 students in control group and experiment group. From the research conducted, researchers can conclude from various processes during the study.This is evidenced by the results of quantitative research on the calculation of the T-test using SPSS Statistics Version 25 which shows the value of t = 13,889 and t table = 2.365, therefore tcount <ttable then with thus H0 is rejected, and H1 is accepted. This means that there is a difference in scores between before and after being given service. This shows that the Self Management Technique given by researchers to group counseling members was able to overcome the problem of delays in handing over assignments during the Covid-19 Pandemic at SMP Nurul Iman Sukakarya.